The problems of developing teaching in the process of work at the artistic form of musical work (Pedagogy of Higher and Secondary Education, 2006)
In the article of training of the future teacher in the process of performance of the vocal-chorus repertotry are considered.
Keywords: conducting; vocal-chorus work